Untitled, 2011 : hybridising performance in mashup practice : a thesis presented in partial fulfilment of the requirements for the degree of Doctorate in Fine Arts at Massey University, Wellington, New Zealand - James, Daniel (Massey University, 2011)
This thesis investigates ‘mashup’ as a mode of creative practice, in relationship to the hybridised notion of ‘performance’. Consisting of a suite of three new creative projects, that each variously encompass facets of mashup in performance practice, the research is presented as multimedia, incorporating video, sound and live performance. The research investigates a number of key theoretical constructs across performance, as well as recent studies of mashups in popular culture and music. Special focus is placed on the work of the performance scholar Jon McKenzie, and his ideas about what constitutes performance in the twenty-first century. His theoretical principles are discussed in relation to performance practices in fine arts and music, and more specifically to my own mashupderived practice. Studies that specifically investigate mashup practice in music are also prescient, and this research emphasises recent and seminal doctoral dissertations by the ethnomusicologist Liam McGranahan and the music theory scholar Christine Boone. In this thesis, I argue for the uniqueness of my mashup-derived performance works (as distinct from other work that already exists in the field), and I argue that ‘performance’ itself needs to be understood in a manner that allows for a greater level of depth and nuance in order to adequately encompass hybridised, multi-mode, multi-context creative practice.
Video file "Breakfast party at my studio" available with hard copy of the thesis in the library
Keywords: Daniel James; Performance art; Mashup; 'Breakfast Party at my Studio'; 'Flight of the Alphabet'; Übermahlung und Frottage